DISEASES DIVERSITY FOR FLAX GENETIC RESOURCES IN LATVIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Flax (Linum usitatissimum L) yield of stem and seeds and them quality is influenced by a number of harmful diseases but investigation about pathogens in recent years have not been done in Latvia. Each stage of development of disease is important in the pathogen life cycle and requires certain condition. Goal of this study have identify possibilities of the pathogens and were assess disease severity depending on the genotypes on flax in variable environmental conditions. The resistance to the diseases for 24 flax genotypes and standard variety ‘Vega 2’ were evaluated. The field trials have been carried out over the period from 2015 to 2016 at the Research Centre of Priekuli, part of Vilani in Latgale. Disease progress was measured every week, and for each treatment, severity of diseases index and the area under the disease progressive curve (AUDPC) were calculated. The flow cytometry method for detection of flax pathogens was developed. The Fusarium avenaveum was dominating disease and statically significant in both vegetation periods. In 2015 were identified statically significant (p